The Effect of A Warm Compress to Decrease the Degree of Menstral Pain in Teenage Girl at Sekip Village, Lubuk Pakam Districts, Deli Serdang Regency 2022 - Basyariah Lubis; Nurmala Sari (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Continuous abdominal muscle contractions due to menstrual bleeding cause dysmenorrhea pain. Menstrual pain or dysmenorrhea is not only the most common problem, but also a cause of reduced activity in women during menstruation, for example not going to school. Non-pharmacological treatment of this problem needs to be developed, such as using warm water compresses. The purpose of this study was to determine the effect of hot water compresses on reducing the intensity of menstrual pain in adolescents in Sekip Village, Lubuk Pakam District, Deli Serdang Regency in 2022. The research used was a pilot study with one group. before and after test design. Based on the inclusion criteria, samples were taken from a total of 30 people using appropriate sampling techniques. Proportion test analysis using paired sample t-test. Data analysis used the Shapiro-Wilk test and the research tool was a pain observation sheet, namely the Numerical Rating Scale (NRS). The results of this study showed that the average pain of dysmenorrhea before applying warm compresses was 6.93, with a median score of 7.00 and a standard deviation of 1.23. The lowest mean score for dysmenorrhea before warm compresses was 4 and the highest score was 9. The average dysmenorrhea pain after warm compresses was 3.90, with a median score of 4.00 and a standard deviation of 1.24. The lowest mean score for dysmenorrhea after warm compresses was 1 and the highest score was 6. There was an effect of warm compresses on the level of dysmenorrhea pain in adolescents in Sekip Village, Lubuk Pakam District, Deli Serdang Regency (?=0.000). It is hoped that warm compresses can be practiced as a treatment to relieve menstrual pain (dysmenorrhea) in adolescents who experience menstrual pain (dysmenorrhea).